IMPLEMENTASI KEGIATAN LITERASI PAGI SERTA DAMPAKNYA TERHADAP PENINGKATAN KETERAMPILAN MEMBACA SISWA SDN 08 PEMULUTAN BARAT - Suryatina, Suryatina (Jurnal Multidisipliner Bharasumba, 2024)
This research investigates the implementation and impact of the morning literacy program at State Elementary School (SDN) 08 Pemulutan Barat. The aim is to evaluate the effectiveness of the program in improving students' reading abilities. The research method is a qualitative method including participatory observation of program implementation, data analysis from pre- and post-program reading tests, as well as interviews with teachers or homeroom teachers at SDN 08 Pemulutan Barat. The research results showed a significant increase in students' reading skills after participating in the morning literacy program. However, obstacles such as limited resources and lack of awareness of the importance of literacy remain challenges during program implementation. This research concludes that the morning literacy program is effective in improving elementary school students' reading skills, but requires further attention to supporting factors such as resource allocation and awareness of the importance of literacy in the implementation process. The implication of this research is the importance of developing educational strategies and policies that strengthen literacy at the elementary school level.